Insights into the function of NADPH thioredoxin reductase C (NTRC) based on identification of NTRC-interacting proteins in vivo. (10th July 2019) - González, Maricruz; Delgado-Requerey, Víctor; Ferrández, Julia; Serna, Antonio; Cejudo, Francisco Javier
Abstract : The identification of NTRC partners in vivo confirms the interaction of NTRC and 2-Cys PRX in Arabidopsis plastids and provides further evidence for a role for NTRC in chloroplast redox regulation. Abstract: Redox regulation in heterotrophic organisms relies on NADPH, thioredoxins (TRXs), and an NADPH-dependent TRX reductase (NTR). In contrast, chloroplasts harbor two redox systems, one that uses photoreduced ferredoxin (Fd), an Fd-dependent TRX reductase (FTR), and TRXs, which links redox regulation to light, and NTRC, which allows the use of NADPH for redox regulation. It has been shown that NTRC-dependent regulation of 2-Cys peroxiredoxin (PRX) is critical for optimal function of the photosynthetic apparatus. Thus, the objective of the present study was the analysis of the interaction of NTRC and 2-Cys PRX in vivo and the identification of proteins interacting with them with the aim of identifying chloroplast processes regulated by this redox system. To assess this objective, we generated Arabidopsis thaliana plants expressing either an NTRC–tandem affinity purification (TAP)-Tag or a green fluorescent protein (GFP)–TAP-Tag, which served as a negative control. The presence of 2-Cys PRX and NTRC in complexes isolated from NTRC–TAP-Tag-expressing plants confirmed the interaction of these proteins in vivo . The identification of proteins co-purified in these complexes by MS revealed the relevance of the NTRC–2-Cys PRX system in the redox regulation of multiple chloroplast processes. The interaction of NTRC with selected targets was confirmed in vivo by bimolecular fluorescence complementation (BiFC) assays.